Web Analysis of 4ICU and Webometrics Based on University Ranking using Web Impact Factor (Universitas Negeri Semarang, 2019)
The university ranking is currently used as a measurement standard for the development of universities in the world or referred to as World Class University (WCU). Many universities in Indonesia use ranking websites as their credible ranking benchmark. This research tries to compare two flagship ranking websites, Webometric and 4ICU which are frequently used as the main ranking standards in Indonesia. The Webometrics itself has four types of parameters for the measurement, namely Size (20%), Visibility (50%), Rich Files (15%), and Scholar (15%), while 4ICU uses two parameters: Google Page Rank and Alexa Traffic Rank. The results of the Web Impact Factor analysis show that Universitas Alma Ata has the lowest web page ranking with a total score of 144. The results are obtained by combining internal and external links in the web domain: almaata.ac.id. The Google links connected to the Universitas Alma Ata website have 25 backlinks taken from the web crawlers. The web impact factor value obtained from the web impact factor (WIF) formula is 0.005. The WIF values obtained from twenty universities have the same significant results or accepts Ho because the probability value for 2 = 1.03 F c is 0.5975, where the probability has higher value than a = 0.05. There should be a number of websites that can support existing backlinks on university websites.